(untitled) (Research, Society and Development, 2021)
Spices are a rich source of polyphenols and when consumed regularly in the diet contribute to the beneficial health effects of these bioactive compounds. The aim of this study was to elaborate a baked product, honeybreads, without spices, control honeybread (CHB) and with ) the addition of spices, spiced honeybread (SHB, estimate their polyphenol content and evaluate their sensory acceptance. The macronutrient composition was calculated using the Brazilian Food Composition Database and phenolic compounds content calculated based on Phenol-Explorer 3.0 database. For sensory evaluation, a consumer panel was established, and a seven-point structured hedonic scale applied for: aroma, texture, appearance, taste and total acceptance. Each formulation yielded seventy 16g servings with similar calories. The total phenolic compound content, per serving, of SHB was 11,198mg and for CHB 9,483mg, content approximately 18% higher with the addition of spices. Both formulations showed good acceptability based on the acceptability index with over 75% on every parameter. Selection of specific ingredients can positively impact polyphenol content in baked products without compromising sensory characteristics.